Development of the modified corporate risk disclosure index for business sustainability / Nur Syahira Rashadan ... [et al.] - Rashadan, Nur Syahira; Joseph, Corina; Hamid, Muhammad Hariz; Syed Yusuf, Sharifah Norzehan (Universiti Teknologi MARA, Kedah, 2025)
The paper aims to outline the development of the Modified Corporate Risk Disclosure index. Its primary objective is to assist organizations in the case of oversight and monitoring of strategies to achieve long-term business sustainability. The Modified Corporate Risk Disclosure Index, comprising 134 items, is designed to serve as a detailed and comprehensive checklist for evaluating the level of corporate risk disclosure in corporations' annual reports. It is anticipated that the Modified Corporate Risk Disclosure Index will elevate companies’ level of corporate risk disclosure by highlighting the advantages of having such an index. The benefit of creating this index is to establish a comprehensive framework that ensures long-term sustainability of the business and emphasizes transparent communication of potential risks to facilitate oversight and evaluation of the company's strategy.